2020
DOI: 10.1136/vetreccr-2020-001086
|View full text |Cite
|
Sign up to set email alerts
|

Atypical case of parietal fibrinous peritonitis in a Belgian Blue heifer without a history of laparotomy

Abstract: A 19-month-old Belgian Blue heifer was referred to the Veterinary Clinic of Liege University. The heifer was 2 months pregnant by insemination and presented hyperthermia, anorexia and weight loss. Rectal palpation revealed a large, depressible abdominal mass. Diagnosis of parietal fibrinous peritonitis (PFP) was made by ultrasound, revealing a liquid and fibrin filled cavity attached to the abdominal wall. Blood analysis indicated an inflammatory status. Analysis of a PFP fluid sample confirmed bacterial conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(61 citation statements)
references
References 10 publications
1
60
0
Order By: Relevance
“…This study presents a unique dataset containing a large number of PFP cases observed in the field. Only very few studies have reported aerobic or anaerobic bacteria, BoHV4 and M. bovis in peritoneal liquids and, particularly, in cases of PFP [ 2 , 3 , 4 , 15 ]. To our knowledge, the presence of C. burnetii in peritoneal fluids has never been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study presents a unique dataset containing a large number of PFP cases observed in the field. Only very few studies have reported aerobic or anaerobic bacteria, BoHV4 and M. bovis in peritoneal liquids and, particularly, in cases of PFP [ 2 , 3 , 4 , 15 ]. To our knowledge, the presence of C. burnetii in peritoneal fluids has never been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…This number may even be an underestimation of the true presence, due to the limited sensitivity of bacteriological culture. Also, it is very likely that several cows had been treated with antimicrobials before sampling, modifying the culture results [ 2 , 4 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations